Arduino Uno, Microcontroller Trainer, 4D Model, TELOS, Vocational Education, learning media. - Suyatmo; Andono, Candra Riyan Andono; Pambudiyatno , Nyaris (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
In vocational education, particularly in aircraft maintenance engineering, the mastery of microcontroller systems requires both theoretical knowledge and hands-on practice. However, limited laboratory equipment and inadequate learning media at the Surabaya Aviation Polytechnic have created a gap between theory and practice, restricting students’ opportunities to apply programming and microcontroller concepts effectively. To address this research gap, this study aimed to design and evaluate an Arduino-based microcontroller trainer module as a practical learning tool for the Diploma 3 Aircraft Maintenance Engineering program. The research adopted the Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). Two expert validators and 19 students participated as research subjects. The trainer module was designed using Arduino Uno ATMega328, integrated with sensors, actuators, and display components to support diverse experiments in programming and control systems. Validation was conducted using the TELOS framework, while effectiveness was measured through pre-test and post-test evaluations of student performance. The validation process confirmed that the trainer achieved a feasibility score of 90.95%, placing it in the “Very Feasible” category. Student assessments also indicated high usability and practicality, with an average user validation score of 91.22%. Furthermore, the implementation results demonstrated significant improvement in learning outcomes. The average pre-test score of 50.53 (“Poor”) increased to 77.37 (“Good”) in the post-test, representing a 53.11% improvement in performance. These findings confirm the thesis that the developed trainer module is a valid, practical, and effective learning medium for supporting microcontroller education in vocational programs. The research highlights the importance of integrating structured trainer modules into aviation engineering curricula to bridge the gap between theoretical instruction and practical application.